Romantic Love: A Patchwork - Caraway, Carol (Philosophy & theology, 1987)
I defend my earlier nonessenlialist analysis of romantic love as involving concern, the passion for union, the desire for reciprocation, admiration, and idealizalion. No central element unifies the analysis. Though not parts of romantic love, sexual desire and exclusivity enhance and generally accompany it. I argue that my analysis is superior to one with a unifying central element. For by allowing variation and conflict among the elements of romantic love, my analysis better explains its turbulence and voIatility and accommodates both realism and idealism.